2017
DOI: 10.1016/j.laa.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Compressed sensing for finite-valued signals

Abstract: The need of reconstructing discrete-valued sparse signals from few measurements, that is solving an undetermined system of linear equations, appears frequently in science and engineering. Whereas classical compressed sensing algorithms do not incorporate the additional knowledge of the discrete nature of the signal, classical lattice decoding approaches such as the sphere decoder do not utilize sparsity constraints.In this work, we present an approach that incorporates a discrete values prior into basis pursui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…The algorithm then chooses the solution which is closest to being binary-valued. In [11] it has also been shown, that one of the solutions is indeed exactly binary, provided we have sufficiently many measurements. However, this algorithm can only succeed in the case that only one of the solutionsx 1 andx 2 is binary.…”
Section: Mirrored Binary Basis Pursuit With Box Constraintsmentioning
confidence: 78%
See 3 more Smart Citations
“…The algorithm then chooses the solution which is closest to being binary-valued. In [11] it has also been shown, that one of the solutions is indeed exactly binary, provided we have sufficiently many measurements. However, this algorithm can only succeed in the case that only one of the solutionsx 1 andx 2 is binary.…”
Section: Mirrored Binary Basis Pursuit With Box Constraintsmentioning
confidence: 78%
“…This experiment is specified in Subsection 2.2. (b) In [11,14] theoretically proven phase transition of (P bin ) in comparison to the classical algorithm (P + ) and (P 1 ) for arbitrary N ∈ N. Successful Reconstruction is guaranteed in the area above the curves with high probability. Figure 1: Numerically and theoretically derived phase transition of (P bin ) from Gaussian measurements.…”
Section: Reconstruction Of Binary Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…More generally, the discrete tomography problem can be regarded as reconstructing a discrete-valued synthesis/analysis-sparse signal from few measurements which is observed by deterministic sensors A. This is, in turn, a special instance of the compressed sensing problem [7], for which it has been shown that discreteness constraints on the possible values of the reconstructed function can significantly reduce the number of required measurements [10]. However, the discreteness constraint leads to great computational challenges.…”
Section: Introductionmentioning
confidence: 99%